Efficient priority rules for the resource-constrained project scheduling problem - Rainer Kolisch (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
We review the well-known RSM priority rule to solve the resource constrained project scheduling problem. A detailed analysis of this rule reveals that it is based on assumptions which do not hold in general and hence might lead to poor solutions. Consequently, an improved RSM priority rule is derived. Furthermore, two new priority rules are developed which extend the well-known precedence based minimum slack priority rule (MSLK) to a precedence and resource based slack priority rule, respectively. An experimental investigation on the basis of two instance-sets from the open literature shows that the new rules outperform all other priority rules which were proposed so far.
Keywords: 650; Resource-Constrained Project Scheduling; Parallel Scheduling Scheme; Priority Rules; Single-Pass Heuristics; Experimental Evaluation; Produktionssteuerung; Theorie